Penyusunan Standar Kompetensi Sosio Kultural Untuk Jabatan Pimpinan Tinggi Di Pemerintahan Daerah - Dewi Sartika (Jurnal Transformasi Administrasi, 2016)
Managing human resources personnel is one of the areas of change bureaucratic reform. Thereby improving the quality of civilian state apparatus becomes the main focus in structuring human resource roadmap. The problems identified in the capacity building of the state civil servants apparatus world class include the need for socio-cultural competence on the state civil apparatus, in particular acting as a high chief or the decision maker in each organization unit. Policy analysis is trying to formulate the dimensions of socio-cultural competence of personnel, which dielborasi of a series of panel discussions with experts, in order to form leaders of character dynamic, adaptive and acceptable in the administration of public services and governmental affairs. Where the results of the discourse can be seen that the formulation of job competency standards can be done through several aspects; (1) Categorizing the level of competency based on relevance. (2) Preparation of standards of competence should consider the development vision of the head of government. (3) The competency standards prepared by considering the purpose of implementation, the executing agency, strength of character, competence, environment and culture, community, quality of service, mental revolution, integration competency standards with ASN management, intelligence and balance.